2012
DOI: 10.1055/s-0032-1311767
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Treatment of Scaphoid Fractures and Their Complications

Abstract: The scaphoid is the most commonly fractured carpal bone, with frequent complications that are predisposed by its anatomical location, anatomical configuration (shape and length), and vascular supply. The most common mechanism of injury is a fall onto an outstretched hand. Imaging plays a significant role in the initial evaluation and treatment of scaphoid fractures and their complications. Radiography should be the first imaging modality in the initial evaluation and follow-up of scaphoid fractures. Computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 69 publications
0
9
0
2
Order By: Relevance
“…Any fracture that persists for longer than six months is considered a nonunion [3]. Non-union can show a distinct pattern of degenerative changes, eventually leading to a scaphoid non-union advanced collapse wrist [4]. In established non-union, the treatment goal, in addition to bone union with restoration of the shape of the scaphoid, should be to re-establish wrist function so that the patient can resume normal activities [5].…”
Section: Introductionmentioning
confidence: 99%
“…Any fracture that persists for longer than six months is considered a nonunion [3]. Non-union can show a distinct pattern of degenerative changes, eventually leading to a scaphoid non-union advanced collapse wrist [4]. In established non-union, the treatment goal, in addition to bone union with restoration of the shape of the scaphoid, should be to re-establish wrist function so that the patient can resume normal activities [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to Taljanovic et al 29 CT allows better visualisation of fracture line, displacement and angulation of fracture fragments, and MRI without contrast is the investigation of choice for diagnosing occult scaphoid fractures. Bretlau 4 in his study concluded that scaphoid fractures can be diagnosed earlier, using dedicated-extremity MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Der Frakturverlauf im Verhältnis zur Längsachse wurde von Russe als Instabilitätskriterium herangezogen [5]. Horizontal-oder querverlaufende Frakturen haben eine bessere Heilungsprognose als vertikale Frakturen [3,17].…”
Section: Frakturverlaufunclassified
“…Frakturen des Kahnbeins sind mit etwa 70-80 % die häufigsten Frakturen der Handwurzel [1]. Sowohl die komplexe Form des Kahnbeins als auch die retrograde Blutversorgung erschweren die Heilung, wodurch es häufig zu Pseudarthrosen und letztlich zum karpalen Kollaps kommt [2,3].…”
Section: Introductionunclassified